EFEK KONSUMSI BIO-YOGHURT DARI LACTOBACILLUS RHAMNOSUS SKG34 TERHADAP LIPID PROFILE PADA MANUSIA - I Desak Putu Kartika Pratiwi; Komang Ayu Nocianitri; Wayan Redi Aryanta; Yan Ramona; I Dewa Made Sukrama; I Nengah Sujaya (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2013)
This research was carried out to elucidate the eff ect of consumption bio-yoghurt produced byLactobacillus rhamnosus SKG34 on plasma lipid profi les in human. The study was performed usingpre and post analysis. Eleven healthy volunteers aged between 30-48 yeras old were participatedin this study. Each volunteers consumed 100g of bio-yoghurt containing L.rhamnosus SKG34 for 21 days. Blood samples were taken before the start of experiment and after 21 days of comsumption. Total cholesterol was measured using CHOP-POD method, while triglyceride determinedusing glycerol method, LDL and HD determined using homogenous method. Results of thestudy revealed that consumption of the bio-yoghurt lower values of plasma lipid concentrationsin hypercholesterolemia subjects. Total cholesterol, triglyceride and LDL was reduced within4.91%, 13.84%, and 8.24%, respectively, when compare to its concentrations before treatment.However, the plasma lipid concentrations in normal subjects were almost stable during thetreatment periods. Consumption of bio-yoghurt for 21 days had no eff ect on HDL-cholesterollevel. These results indicate that consumption of bio-yoghurt containing L.rhamnosus SKG34specifi cally lowered the concentrations of serum total cholesterol, LDL, and triglyceride onhypercholesterolemia subjects.